ANALISIS PENGEMBANGAN KARIR ASN BERDASARKAN MERIT SISTEM (STUDI PENELITIAN DI PEMERINTAH KABUPATEN ACEH TENGAH) - Hasan Basri; Jusmadi Sikumbang; Agusmidah Agusmidah; Suhaidi Suhaidi (USU LAW JOURNAL, 2018)
ABSTRACT   The enactment of Law Number 5 Year 2014 on ASN is expected to bring significant changes in institutional, career and remuneration systems as this law revolutionizes the recruitment, development and career development system which includes a career path and high filling system through open promotion. The government realizes that bureaucracy is an important and major factor in a bureaucratic administration administration, in which a State Civil Apparatus (ASN) plays a very important role in it. To ensure the election of professional and competent persons, in accordance with the standard of competence of office. Central Aceh district which is one of the areas located in the province of Aceh is an area where the level of productivity of public services is still low, the civilian state of the existing country more comes from people close to the leadership. As for the problem in this research is How the provision of career development ASN based on system merit ?, Is the existing regulation able to build mechanism and institute for career development ASN based on merit system ?, How Regency of Aceh Tengah implementing merit system in filling position / career ASN? This type of research used is the juridical approach normative or doctrinal. Sources of Legal Materials to be used are Primary Legal Material, Secondary Legal Material, and Tertiary Law Material. Techniques and Data Collection Tools that researchers use is Document Studies. The data has been collected and then analyzed by using descriptive qualitative analysis, which is analysis by describing and analyzing the data of literature and field data in the form of statement carefully and systematically. The results of this study indicate that the development of ASN careers based on system merit refers to based on Law No. 5 of 2014 About ASN is a system of personnel development based on career and work performance, measurable administratively and the reality of the achievement of duties and devotion of an employee, in the duty environment which he assumed in the organization of government office. Regulations or legislation governing the provisions relating to the State Civil Apparatus that is in Law No. 5 of 2014 and Government Regulation No. 11 of 2017 on the State Civil Apparatus Management for the present become the basis for the government both central and local as a foundation of career development and development ASN or Civil Servant. It's just that the regulation has not run optimally and optimal because it has not been able to overall local government to implement the merit system in ASN career development. The implementation of ASN careers and career development in the regency of Central Aceh is not currently running optimally and optimally, because there is still influence by the officials concerned.   Keywords: Career Development, Merit system, State civil apparatus